Aisnusantara: Kontribusi Santri Membangun Narasi Damai di Era Digitalisasi Media - Illiyyun, Naili Ni'matul; Anshori, Ahmad Afnan; Suyanto, Helmi (JSW (Jurnal Sosiologi Walisongo), 2020)
Instagram has become a new lifestyle in recent years. Instagram has created a society without borders because its users and followers are not limited to places. Instagram users post creative photos and videos on their accounts not only for advertising but also network orientation. Millennial generation tends to use the internet in all aspects of life. This paper aims to pay attention to: 1) How about the model and strategy of the Millennial Muslim network in aisnusantara; and 2) How they explain the importance of religious moderation in digital media. This qualitative research uses a netnographic approach based on data from the @aisnusantara Instagram account. With the ethno-semiotic method, this research reveals that: 1) Aisnusantara uses a networking management model from the national to regional levels, and has an annual meeting, namely the Kopdarnas which has an agenda to discuss various issues related to national and religious affairs for the millennial generation. 2) Aisnusantara campaigned for Islamic preaching inclusively through Instagram, for example against extremism on social media, by offering alternative narratives to counter extremism by campaigning for peaceful Islam based on religious moderation.